EFFECT OF EXPORT IMPROVEMENT POLICY THROUGH EXPORT-ORIENTED CREDIT BUSINESS PROGRAMS ON EXPORT GROWTH OF MICRO SMALL MEDIUM ENTERPRISES IN 2016 - Selina Tikau (Sociae Polites, 2018)
Kredit Usaha Rakyat Berorientasi Ekspor (KURBE) is a program aimed at increasing the export of Micro, Small and Medium Entreprises (MSME). KURBE is an implementation of the economic policy volume 11. Credit Financing is given, especially for MSME that has export-oriented. KURBE had not to provide an influence on MSME export growth in 2016. KURBE program faced many obstacles that made its program less effective. Using qualitative methods, we viewed distribution KURBE and its influence on export growth.